Hyperglycemia in transported neonates: A tertiary care experience - Mishra, Nihar Ranjan; Sahoo, S K; Panda, S (Indian Journal of Child Health, 2022)
Introduction: Hyperglycemia is common in low birth weight and sick neonates which affect them adversely due to hyperosmolarity. As these neonates need often referral to higher setup, maintenance of euglycemia during transport should be emphasized. Objective: To know the prevalence of hyperglycemia on admission among outborn neonates and analyze the association of different transport variables and other clinical parameters with it. Methods: An observational, analytical, and cross-sectional study was designed and conducted on outborn neonates, enrolled by simple consecutive sampling from November 2014 to October 2016. All data were analyzed using SPSS version 24 and Microsoft Excel version 16 software. Results: Out of 394 outborn neonates, 33.75% were hyperglycemic. 76.4% newborns were transported by ambulance, 94.9% were stabilized before referral, 61.2% had accompanying paramedics, 86.5% neonates given intravenous fluid (IVF) during transport, 61.4% transported by moderately equipped, and 38.6% by poorly equipped vehicle. Admission hyperglycemia was significantly associated with variables such as gestational age, birth asphyxia, type of transport vehicle, duration of transport, IVF during transport, hypoxic ischemic encephalopathy, and neonatal jaundice with p